Monitoring of Organic Acids in Ginseng Roots Produced by Conventional and Environmentally Friendly Farming by Gas Chromatography–Mass Spectrometry. (3rd December 2018) - Seo, Chan; Kim, Donghyun; Kim, Youngbae; Lee, Hyeon‐Seong; Kim, Hyunbin; Park, Kyung Wuk; Oh, Dong‐Joo; Park, Junseong; Yang, Deok‐Chun; Paik, Man‐Jeong
Abstract : Metabolomic analysis of organic acids has not been performed for evaluation whether ginseng has been cultivated using conventional or environmental‐friendly farming methods. In this study, profiling analysis was conducted for organic acids (OAs) in ginseng roots produced using conventional or environment‐friendly farming methods at five locations in each of five regions. In OA profiles, lactic acid was the most abundant OA in all regions, with the exception for environmentally friendly farmed ginseng in two of the five regions, in which glycolic acid was most abundant OA. OA profiles in all regions showed isocitric acid levels were increased by environment‐friendly cultivation, which suggests metabolic differences associated from farming method, and that isocitric acid might be a useful discriminatory biomarker of environmental‐friendly and conventional cultivation. The results of the present study suggest metabolomic studies of OAs in ginseng roots might be useful for monitoring whether ginseng has been cultivated using conventional or environmentally friendly farming methods. Abstract :